Discovering the dynamics of microbial genomes. - Dalevi, D. (IEEE Engineering in medicine and biology magazine)
Although the molecular processes that generate genome diversity at the sequence level have been described in great detail, the underlying causes of genome expansion, degradation, rearrangement, and transfer of genes are less well understood. In this article, we describe the algorithms most frequently used to infer evolutionary relationships based on nucleotide sequence data. We also discuss novel phylogenetic schemes where the gene in the genome, rather than the nucleotide in the gene, represents the basic unit of comparison